1995
DOI: 10.1002/ijc.2910620217
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by dehydroepiandrosterone of growth and progression of persistent liver nodules in experimental rat liver carcinogenesis

Abstract: Dehydroepiandrosterone (DHEA) inhibits the development of early pre-neoplastic lesions and prevents tumor development in various tissues when given to animals during the initiation/promotion stages of carcinogenesis. Our purpose was to evaluate whether DHEA can also arrest the growth and progression of late lesions, such as persistent nodules (PNs) of rat liver. Male F344 rats were subjected to initiation by diethylnitrosamine followed by selection according to the "resistant hepatocyte" (RH) protocol. Fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…DHEA gained special interest in cancer research because of its anticarcinogenic properties proven in various organs of laboratory rats including the liver (34,35,43; summarized in 7,19). Conversely, DHEA showed unfavorable effects in rat liver such as hepatomegaly and peroxisome proliferation, and after long-term treatment hepatocellular carcinomas developed (10,24,31,32,33).…”
Section: Introductionmentioning
confidence: 99%
“…DHEA gained special interest in cancer research because of its anticarcinogenic properties proven in various organs of laboratory rats including the liver (34,35,43; summarized in 7,19). Conversely, DHEA showed unfavorable effects in rat liver such as hepatomegaly and peroxisome proliferation, and after long-term treatment hepatocellular carcinomas developed (10,24,31,32,33).…”
Section: Introductionmentioning
confidence: 99%
“…G6PD activity was found to increase upon stimulation by growth factors in fibroblasts (Stanton et al, 1991), adipocytes (Teruel et al, 1996), and hepatocytes (Yoshimoto et al, 1983). The induction of G6PD activity was also detected in the tumors of several animal models of carcinogenesis, including diethylnitrosamineinduced liver tumors in rats (Simile et al, 1995) and estrogeninduced kidney tumors in hamsters (Roy and Liehr, 1988). Furthermore, a significant increase of G6PD activity was found in many naturally occurring tumors including breast carcinoma (Bokun et al, 1987), endometrial carcinoma (Hughes, 1976), cervical carcinoma (Dutu et al, 1980), prostatic carcinoma (Zampella et al, 1982), and lung tumors (Dessi et al, 1988).…”
mentioning
confidence: 99%
“…Additionally, DHEA treatment has been shown to retard the onset of chemically induced cancers such as mammary, liver and prostate carcinogenesis in experimental rat models (Simile et al, 1995;Lubet et al, 1998;Rao et al, 1999). More recently, Yoshida et al (2003) reported that DHEA and its metabolites have antiproliferative effects on human hepatoma and human colonic adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%